ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA ZAKAT, INFAK/SEDEKAH PADA YAYASAN BAITUL MAAL BRILiaN REGIONAL OFFICE MANADO - Sadjiman, Vidya Putri; Saerang, David P. E.; Warongan , Jessy D. L. (Universitas Sam Ratulangi, 2023)
This study aims to describe the phenomenon of accountability for zakat management at the Zakat Foundation called YBM BRILiaN who basically distributed zakat gacor slot fund from muslim employees in BRI. The qualitative research method with a case study approach is used to describe the accountability of zakat management at YBM BRILiaN in Regional Office Manado. The object of this gacor slot research is YBM BRILiaN Regional Office Manado who handled distributed of zakat fund in four provinces, those are North Sulawesi, Central Sulawesi, Nort Maluku and parts of West Sulawesi. The Data were collected through interviews with informants. The phenomena encountered are then analyzed and described using Islamic paradigm and the theory of public accountability and indicators of transparency. The results showed that zakat management at YBM BRILiaN in whole has been accountable because the processes gacor slot that implementing from the mapping the budget until the reporting already followed the standard operating procedures who made by the decision of rules of government and consideration with all parties involved. The website dan social media owned by YBM BRILiaN become source of information about activities, program and also report of zakat management.